Exhausted T cells in systemic lupus erythematosus patients in long-standing remission. (28th February 2021) - Lima, G; Treviño-Tello, F; Atisha-Fregoso, Y; Llorente, L; Fragoso-Loyo, H; Jakez-Ocampo, J
Summary: The mechanisms that drive systemic lupus erythematosus (SLE) patients to achieve remission are unknown; one possible explanation might be T cell exhaustion. The aim of the present study was to measure CD4 + and CD8 + T cell exhaustion in SLE patients in prolonged remission (PR-SLE) and compared them with patients with active SLE (Act-SLE) and healthy subjects. We included 15 PR-SLE patients, 15 Act-SLE and 29 healthy subjects. T cell exhaustion was determined by flow cytometry according to the expression of programmed cell death 1 (PD)-1, T cell immunoglobulin and mucin 3 (Tim-3), natural killer cell receptor (2B4), eomesodermin (EOMES) and T-box transcription factor TBX21 (T-bet) in CD4 + and CD8 + T cells. Dimensionality reduction using the T-distributed stochastic neighbor-embedding algorithm and clustering analysis was used for the identification of relevant populations. Percentages of CD3 +, CD4 + and CD8 + T cells were similar among groups. We identified five subpopulations of CD8 + and seven of CD4 + cells. The CD4 + T-bet + CD45RO + cells identified in the unsupervised analysis were significantly increased in PR-SLE versus Act-SLE [median = 0·20, interquartile range (IQR) = 1·74–30·50 versus 1·68, IQR = 0·4–2·83; P < 0·01]. CD4 + EOMES + cells were also increased in PR-SLE versus Act-SLE (5·24, IQR = 3·38–14·70 versus 1·39, IQR = 0·48–2·87; P < 0·001). CD8 + EOMES + cells were increased in PR-SLE versus Act-SLE (37·6, IQR = 24·9–53·2 versus 8·13, IQR = 2·33–20·5; P < 0·001). Exhausted and activated T cells presented an increased frequency of PD-1, CD57 and EOMES in SLE patients versus healthy subjects. Some subpopulations of T cells expressing markers associated with exhaustion are increased in patients in remission, supporting T cell exhaustion as a tolerance mechanism in SLE. Exhaustion of specific populations of T cells might represent a potential therapeutic tool that will contribute to the goal of achieving sustained remission in these patients. Graphical Abstract: